Money, Food, and Daily Life Objects Are Similarly Shared in the Dictator Game. A Study among Poles and Tsimane’ - Sorokowski, Piotr; Oleszkiewicz, Anna; Niemczyk, Agnieszka; Marczak, Michalina; Huanca, Tomas; Velasco, Esther C.; Sorokowska, Agnieszka (Frontiers in Psychology, 2017)
The Dictator Game (DG) is one of the most popular methods for measuring sharing behaviors. However, the matter of goods used in the game has rarely been examined and discussed. We conducted a study in which all participants played standard version of DG in one of the three versions – “money”, “food”, or “daily life objects” sharing. Further, we wanted to expand the generalizability of our findings by investigating whether patterns in sharing various goods are independent of culture and the level of market integration. Thus, the study was conducted among people who function daily under the conditions of low market integration (109 Tsimane’ – forager-horticulturists from Bolivian Amazon) and in a society highly integrated with the market-based economy (85 Polish people). We observed that among both Polish and Tsimane’ people the participants were equally likely to share money, food and small, daily life objects with an unknown partner, which implies that generosity might not be related with the type of possessed resources. However, regardless of the kind of goods given, Tsimane’ people were less eager to share with anonymous others than Polish people. We present several implications of our findings for studies on generosity and altruism.